2008
DOI: 10.4028/www.scientific.net/amr.33-37.121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Size and Location of a Weld Defect on Fatigue Life for Argon-Arc Welded Titanium Alloy Joint

Abstract: Analytical studies were made on effect of size and location of a weld defect on fatigue life for argon-arc welded titanium alloy joint. In the analyses, a weld defect was assumed as an initial crack, and the crack growth life was taken as total fatigue life. By using the Isida and Noguchi’s stress intensity factor solution for a plate containing an embedded elliptical subsurface crack under tension, the life prediction code FASTRAN3.9 was revised. A small crack methodology based on the plasticity-induced crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…4(b)), the fatigue life was increased from 155,354 cycles to 213,009 cycles. This result was similar to that by Liu et al [5]. The experimental results demonstrate that the location of the LOF defect had an influence on the fatigue life of the specimens.…”
Section: Resultssupporting
confidence: 91%
“…4(b)), the fatigue life was increased from 155,354 cycles to 213,009 cycles. This result was similar to that by Liu et al [5]. The experimental results demonstrate that the location of the LOF defect had an influence on the fatigue life of the specimens.…”
Section: Resultssupporting
confidence: 91%
“…As shown in Fig. 6a) and by Fan et al [6] and Liu et al [7], small internal pores are less detrimental than surface pores. Three transverse TIG samples had crack initiation at the surface with no visible defects.…”
Section: Proceedings Of the 13th World Conference On Titaniummentioning
confidence: 62%
“…In case the distance from the surface is in the order of the pore's largest dimension, the effect of a surface on plastic strain levels out. Liu et al [7] showed that the fatigue life of titanium alloy welds decreases as the pore size increases and the distance to the surface decreases. In their simulation for pore sizes of 50-100 µm, the effect of distance increased sharply when the distance to a surface decreased below 400 µm.…”
Section: Proceedings Of the 13th World Conference On Titaniummentioning
confidence: 99%